2005
DOI: 10.2308/iace.2005.20.3.231
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Effective Teaching in Accounting on Student Attitudes, Behavior, and Performance

Abstract: In 1993 the School of Business at a large midwestern university established a task force to redesign its introductory accounting/business course. The task force shared many goals of the contemporaneous Accounting Education Change Commission, which addressed desirable attitudes and behaviors for the profession. Although approaches to knowledge and skill development are well understood at universities, much less is known about the impact of effective accounting education on student attitudes and behavior. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 13 publications
2
32
1
Order By: Relevance
“…Heck et al (2002) did consider this issue for finance students, although they reported that better 'perceived' teaching did not lead to higher performance. However, Shaftel and Shaftel (2005) in accounting and Tuckman (1975) in macroeconomics found that effective teaching can improve performance and student attitudes. It should be noted that these papers examine only partially the importance of exogenous factors as they use only one variable (i.e.…”
Section: Exogenous Factorsmentioning
confidence: 95%
“…Heck et al (2002) did consider this issue for finance students, although they reported that better 'perceived' teaching did not lead to higher performance. However, Shaftel and Shaftel (2005) in accounting and Tuckman (1975) in macroeconomics found that effective teaching can improve performance and student attitudes. It should be noted that these papers examine only partially the importance of exogenous factors as they use only one variable (i.e.…”
Section: Exogenous Factorsmentioning
confidence: 95%
“…Schuman, Walsh, Olson and Etheridge (1985) examined group studying, cramming, degree of note-taking, review of past exams, and going over readings twice, but they concluded that none of these variables have been found to have a direct effect on grades. On the other hand, positive results were found when some combination of study behaviors such as attendance, homework turned in, and use of study guide, prior preparation for the class, participating in class, and coming to class on time were used (Gracia, 2003;Shaftel, 2005;Wooten, 1998 ). Group learning activities can result to an increase in students' deep learning approach, which has been known to improve analytical thinking (Hall, 2004 ).…”
Section: Importance Of Study Habits Constructsmentioning
confidence: 99%
“…T-tests for differences in mean importance for the two groups and sensitivity analysis for differences due to size and industry classification were reported. Shaftel and Shaftel (2005) examined the relationships between self-reported attitudes and behaviors related to study-skills and the effect of a new course model (large, instructor-led lectures and smaller, assistant-led sections) on change in study-skills attitude. Students enrolled in an introductory business and accounting course were asked to complete a survey at the beginning and end of the semester, yielding 363 matched pre-and posttests out of 500 students.…”
Section: Student Skills and Characteristicsmentioning
confidence: 99%